VALIDASI METODE ANALISA KADAR FENOLIK EKSTRAK ETANOL DAUN SIRIH MERAH (Piper crocatum) DENGAN MENGGUNAKAN SPEKTROSCOPY UV-VIS - Syahputera, Rony (Program Studi S1 Farmasi, STIKES Senior, Medan, 2024)
Validation research has been carried out on the phenolic content analysis method using the Gallic Acid method on red betel ethanol extract. Red betel leaves in this research were previously characterized microscopically and macroscopically and a phytochemical screening test was carried out to determine the secondary metabolite content in the ethanol extract of red betel leaves. Next, extraction is carried out using the maceration method. The resulting extract is then analyzed to determine the phenolic content in the sample. Determination of phenolic content uses a method that is first calibrated, which includes linearity, LOD and LOQ, precision, accuracy and sensitivity. The results of each analytical parameter analysis are as follows: linearity = 0.9909, precision = 0.046; 0.06; 0.019 recovery = 98 and 102 %, sensitivity = 1.02. 105 L. Mol-1 cm-1. Analysis of the phenolic samples showed a concentration value of 150.04 mg GAE/gram of red betel extract.